Rapid detection of H5 subtype avian influenza virus using CRISPR Cas13a based-lateral flow dipstick - Li, Yang; Shang, Jiajing; Luo, Juan; Zhang, Fuyou; Meng, Ge; Feng, Yingjie; Jiang, Wenming; Yu, Xiaohui; Deng, Chunran; Liu, Guanhui; Liu, Hualei (Frontiers in Microbiology, 2023)
Due to its high mortality rate, highly pathogenic avian influenza (HPAI), a notifiable animal illness designated by the World Organization for Animal Health (WOAH), has caused enormous financial losses to the poultry sector. The H5 subtype of avian influenza virus (H5-AIV) is the most common highly pathogenic avian influenza virus (HPAIV) that threatens public health and safety. Virus isolation and reverse transcription quantitative PCR (RT-qPCR) are usually used to detect H5-AIV and are important for the timely diagnosis and control of H5-AIV. However, these methods require a lot of time, effort, and are challenging to use. In vitro diagnostic tools based on the CRISPR/Cas13a system have been popular in recent years due to their advantages of high specificity, high sensitivity, and low cost. In this study, recombinase-aided amplification (RAA) was combined with CRISPR-Cas13a and lateral flow dipstick (LFD) for the detection of H5-AIV.The working process can be completed on constant temperature. The method has a detection limit of 0.1 copy/μL, which is comparable to the WOAH recommended RT-qPCR, while showing good specificity with no cross-reactivity with H3-AIV, H7-AIV, H9-AIV, H10-AIV, IBV, NDV, RVA and DAstV. A total of 380 clinical samples were detected by RT-qPCR and RT-RAA-Cas13a-LFD.Statistical analysis based on the kappa value (0.89, κ>0.75) for these two assays indicated that no significant difference existed between the assays. In this study, we established a convenient, efficient, and accurate method to detect H5-AIV, and the results can be visualized and interpreted by LFD, which can be adapted to the needs of grassroots laboratories and field-deployable assays, and provides a new way of thinking about clinical H5-AIV diagnosis, and has great potential for application in clinical quarantine of the poultry farming.